Analisis Faktor yang Mempengaruhi Minat Mahasiswa Terhadap Pemilihan Karir Akuntan: Studi Kasus pada Mahasiswa Akuntansi FEB UNTAN - Ayu Umyana; Ira Grania Mustika; Naufal Sadad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the modern era, job opportunities are becoming increasingly diverse and extensive. The abundance of choices and job prospects available undoubtedly leaves accounting students perplexed in determining their future career paths. The aim of this research is to analyze the factors influencing students' interest in choosing a career as an accountant or non-accountant in the Faculty of Economics and Business at Tanjungpura University, Pontianak. The variables used in this study are financial rewards, professional training, and professional recognition as independent variables, while the career as an accountant or non-accountant is the dependent variable. The method used in this research is quantitative method. This research involves hypothesis testing through a survey research using questionnaires. The results of the study show that Financial Rewards do not influence the choice of a career as an accountant, Professional Training does not influence the choice of a career as an accountant, and Professional Recognition has a positive influence on the choice of a career as an accountant. Simultaneously, Financial Rewards, Professional Training, and Professional Recognition have a significant influence on the choice of a career as an accountant.